2004
DOI: 10.1111/j.1365-2141.2004.05077.x
|View full text |Cite
|
Sign up to set email alerts
|

Human γδ T cells as mediators of chimaeric‐receptor redirected anti‐tumour immunity

Abstract: Retroviral gene transfer resulted in chimaeric receptor surface expression in 73 ± 12% of the population. Transduced cd T cells efficiently recognized antigen-expressing tumour cell targets, as demonstrated by target-specific upregulation of CD69 and secretion of interferon-a. Moreover, transduced cd T cells efficiently and specifically lysed the antigen-expressing tumour targets. They could be efficiently expanded in vitro and maintained in culture for prolonged periods. Zoledronate-activated human cd T cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 63 publications
1
93
0
Order By: Relevance
“…However, T cells express low viral receptor levels -integration may be blunted [52] Some successes with TCR transfer, and continue to be used in clinical trials Selective integration is possible [52] CAR, chimeric antigen receptor; IL, interleukin; TCR, T cell receptor; Th1, T helper type 1. tumour immunosurveillance, are cytotoxic to many tumour types and can effectively prime ab T cells. The use of gd T cells also eliminates the risk of chain mispairing, as gd chains would be unable to pair with the introduced TAA-specific ab chains [67]. Evidence has shown that gd T cells show clear anti-tumour effects after transduction [57,67].…”
Section: Adapting Redirected T Cells To Conditions Encountered In Vivomentioning
confidence: 99%
“…However, T cells express low viral receptor levels -integration may be blunted [52] Some successes with TCR transfer, and continue to be used in clinical trials Selective integration is possible [52] CAR, chimeric antigen receptor; IL, interleukin; TCR, T cell receptor; Th1, T helper type 1. tumour immunosurveillance, are cytotoxic to many tumour types and can effectively prime ab T cells. The use of gd T cells also eliminates the risk of chain mispairing, as gd chains would be unable to pair with the introduced TAA-specific ab chains [67]. Evidence has shown that gd T cells show clear anti-tumour effects after transduction [57,67].…”
Section: Adapting Redirected T Cells To Conditions Encountered In Vivomentioning
confidence: 99%
“…Expression of the chRec in SFG-transduced cells was proved by reverse transcription-PCR (RT-PCR). The negative control CD19~chRec was cloned as reported previously (14).…”
Section: Methodsmentioning
confidence: 99%
“…The advantage of retrovirus [63][64][65] or lentivirus 23,36,66,67 to modify populations of T cells lies in the efficiency of gene transfer, which shortens the time for culturing T cells to reach clinically-significant numbers ( Figure 2). Gamma retroviruses, the CAR shown dimerized on the cell surface demonstrating the key extracellular (A-B) and intracellular (C-E) domains.…”
Section: Gene Transfer Of Carsmentioning
confidence: 99%